IMPROVING SPEAKING SKILL OF THE ELEVENTH-GRADE STUDENTS THROUGH THREE STEPS INTERVIEW - Putu Rama Suria Nanda; Ida Bagus Nyoman Mantra; I Gde Putu Agus Pramerta (Academic Journal on English Studies (AJOES), 2023)
This research aims to increase students’ self-confidence in speaking skills by using the Three Step Interview at Eleventh Grade on SMA Negeri 8 Denpasar. This research used Classroom Action Research (CAR) which was taken from Kemmis and McTaggarat’s design. This research was finished in one cycle that consisted of four phases, those were: planning, acting, observing, and reflection. The subject of this research was XI IPA 2 class which consist of 48 students. The method of this research was Three Step Interview which runs into some steps; a) students made a group consisting of 4 persons, b) the teacher gave the topic to the students, c) students were in pairs, one was the interviewer and the other was the interviewee, d) students A interviewed students B and student C interviewed student B, e) students reserved roles and each shared with team member what was learned during the two interviews, f) the teacher gave the reward to the best group. The instruments used in this study were an observation checklist and a questionnaire. This action research was done in two cycles. That got a positive response from the student. There are almost half students agreed to use three steps interview as a teaching method and do some tests on each cycle. The students have a significant improvement. The researchers concluded that this research was successful to increase students’ self-confidence in speaking skills.